A Fresh Defense: A Cultural Biography of Quality in Puerto Rican Fishing. Issue 1 (22nd February 2013) - Griffith, David; García‐Quijano, Carlos; Pizzini, Manuel Valdés
<x xml:space="preserve">Abstract</x> ABSTRACT Puerto Rican artisanal fishers, like artisanal food producers around the world, emphasize the quality of their products to compete with industrial food producer‐distributors. In this article, we trace the cultural biographies of three important fish species, focusing on their roles in creating social relationships and, through this process, creating value and political alliances to contest fisheries laws. We argue that fishers move strategically between moral and political economies to maintain fishing livelihoods and defend themselves against coastal developments that threaten those livelihoods.